Engineering sustainable software: A case study from offline computer support collaborative annotation system - Cheewyai, L.; Cheah, W.; Chowdhury, A.K.; Gulden, C. (2016)
Sustainable software is a software that able to work in a constraint environment. For example, a classroom without Internet facilities or unstable connection; a field trips; a meeting room or discussion room with inadequate computer facilities and power and etc. In this case, how to enabling a daily activity within such situations without losing the benefits of computer support? This paper presents the work to facilitate problem based learning (PBL) among the students at Faculty of Medicine, Unimas through sustainable computer support annotation system. RICAS, is a computer supported collaborative annotation system to promote discussion in a constraint environment. We present the adoption of agent models in conceptulizing a sustainable software and present the design, development and evaluation of the sustainable software in this paper. From the development, we highlight some of the key challenges and solutions when working on the sustainable software.